(3aVGFd SdGWjf Bd YKeGfs - (3GdMehj , CMeO Hf eMeO ecj GdMehj , TgGH GdOjf CHh GdYHGS,J (B1098 (3g` s ((3CMeO CHh UGdM JGHY Hfi GdhaG s)
(3ChdgG (B:s
(3MeOkG def Ndb hCMUGge YOOkG s
(3BNQgG (B:s
(3hbO HQR gPG GdeSWhQ Edi GdhLhO GdcJHi HYO bjGe UhQJg HPgfi hdHi ai CNQjGJ TgQ UaQ ef TghQ (B1095(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B239 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B93s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B114 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs